The whisper man - North, Alex, 1976- (New York : Celadon Books, 2019)
"After the sudden death of his wife, Tom Kennedy believes a fresh start will help him and his young son Jake heal. A new beginning, a new house, a new town. Featherbank. But the town has a dark past. Twenty years ago, a serial killer abducted and murdered five residents. Until Frank Carter was finally caught, he was nicknamed 'The Whisper Man,' for he would lure his victims out by whispering at their windows at night. Just as Tom and Jake settle into their new home, a young boy vanishes. His disappearance bears an unnerving resemblance to Frank Carter's crimes, reigniting old rumors that he preyed with an accomplice. Now, detectives Amanda Beck and Pete Willis must find the boy before it is too late, even if that means Pete has to revisit his great foe in prison: The Whisper Man."--
"A novel" -- Cover.
Keywords: Fathers and sons -- Fiction; Widowers -- Fiction; Serial murderers -- Fiction; Life change events -- Fiction; Boys -- Crimes against -- Fiction; Serial murder investigation -- England -- Fiction; Cold cases (Criminal investigation) -- England -- Fiction; Serial murderers -- Fiction; Psychological fiction; Detective and mystery fiction; Thrillers (Fiction)